Effects of Learning Motivation, Playing Activity, and Parental Care on The Children’s Motor Skill - Yanuar Kiram; Irdas Bakri; Anton Komaini; Damrah Damrah; Ilham Ilham (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
The poor motor skills of children/students of Islamic schools is a fundamental problem of this research. Namely, at the Ibtidaiyah Tahfizh Makkah Siak Hulu Riau Madrasah. Objective: This study aims to reveal the direct and indirect effects, as well as the simultaneous effect of exogenous variables on endogenous variables. Materials and methods: This type of research is quantitative with a path analysis approach. 44 out of 121 students were used in this study by sorting using the purposive sampling technique. Data was collected using a questionnaire (learning motivation, play activity, and parental attention), while data on children's motor skills used Scott's motor skill test. Result: The results showed that: (1) There is a direct effect of learning motivation on play activities (p21 = 0.866, and a contribution of 75%), (2) There is a direct effect of learning motivation on children's motor skills (py1 = 0.304 with a contribution of 9.24%), (3) There is a direct effect of play activity on children's motor skills (py2 = 0.291 with a contribution of of 8.47%), (4) There is a direct effect of parental activity attention on children's motor skills (py3 = 0.425 with a contribution of 18.06%), (5) There is a effect of learning motivation and play activities simultaneously on parental attention (Rsquared = 0.761 with a contribution of 76.1%), (6) There is an indirect effect of learning motivation through parental attention on children's motor skills (p31.py3 = 0.395 > py1 = 0.304 with a total contribution of 48.9%), (7) There is an indirect effect of play activities through parental attention to children's abilities children's motor skills (p32.py3 = 0.416 > p y2 = 0.291 with a total contribution of 50.12%), and (8) there is learning motivation, play activities and parental attention simultaneously on children's motor skills (Rsquared = 0.960 and the Sig value of the ANOVA table is obtained. = 0.002/2 = 0.001 < α = 0.05 or 96%). Conclusion: The results of the study show that learning motivation, playful activities and parental attention have an influence on the motor skills of students of Tahfizh Makkah Madrasah Ibtidaiyah. Nevertheless, further research is needed with larger numbers of samples to further test each variable.